Modeling and simulations of FDSOI five-gate qubit MOS devices down to deep cryogenic temperatures. (July 2022) - Catapano, E.; Aprà, A.; Cassé, M.; Gaillard, F.; de Franceschi, S.; Meunier, T.; Vinet, M.; Ghibaudo, G.
Abstract: FD-SOI five-gate (5G) qubit MOS devices are electrically characterized in linear regime down to deep cryogenic temperatures. The Lambert-W function is successfully used for the modelling of such 5G MOS devices from subthreshold regime to strong inversion. Its applicability is demonstrated down to deep cryogenic temperatures. The 5G device is modeled as a series of five independent transistors: the "active" one, that directly controls the current, and the "external" ones, that act as access resistances. The Lambert-W function enables to accurately reconstruct the inversion charge and the active channel resistance from weak to strong inversion. This approach allows reproducing the drain current characteristic avoiding the evaluation of the mobility attenuation factors. The main device parameters are extracted versus temperature. Furthermore, the role of different scattering mechanisms has been investigated, underlying the impact of defects for the gates in proximity of source and drain. The experimental characterizations have been completed with some Poisson-solver based simulations, carried out down to cryogenic temperatures. In this regime, Maxwell-Boltzmann carrier statistic has been replaced by an analytical expression of the Fermi-Dirac function.